Accuracy of Sysmex XN immature granulocyte percentage compared to manual microscopy - Linko-Parvinen Anna-Maria; Kurvinen Kaisa; Tienhaara Anri (Hong Kong, 2025)
Background: We evaluated autovalidation limit for immature granulocyte percentage (IG%) measured with Sysmex XN (Sysmex Co., Kobe, Japan) to optimize microscopy review for white blood cell (WBC) differential samples. The purpose was to determine if the autovalidation limit can be increased from IG 3%.
Methods: We analysed WBC differential with Sysmex XN and manual microscopy in samples with IG >3% and no other analyser flagging (N=557). The reference samples (N=245) had IG <3% and no analyser flagging. The comparison was based on IG% subgroups. The effect of total WBC and absolute neutrophil count were examined.
Results: Sysmex XN gave median positive error compared to manual microscopy with all IG% levels. The error was higher in subgroups with IG >3% compared to IG <3% (P<0.001). Within IG 3–5.9% subgroups there was no statistically significant difference. The error increased above IG 6%. Neutropenia or neutrophilia did not affect the degree of difference in IG% between the methods (P=0.296). In samples with low WBC, the IG% difference was slightly higher (P<0.001) compared to samples with normal or high WBC.
Conclusions: The positive difference for Sysmex XN IG% is acceptable and clinically not significant up to IG 6%. This autovalidation limit is adequate for reporting IG as a separate parameter (six-part WBC differential). Samples with higher IG% should be reviewed. Autovalidation limit of IG 3% should be used for five-part differential to detect and report neutrophil left shift.
Keywords: Sysmex XN; immature granulocytes (IG); immature granulocytes percentage (IG%)